Co-existence of various clinical and histopathological features of mycosis fungoides in a young female - Farahnaz Fatemi Naeini; Mehrnaz Soghrati; Bahareh Abtahi-Naeini; Jamshid Najafian; Parvin Rajabi (Wolters Kluwer Medknow Publications, 2015)
Mycosis fungoides is the most common type of cutaneous T-cell lymphoma (CTCL) and a rare disorder that typically affects older adults with erythematous scaling patches and plaques. Hypopigmented patches are a rare clinical variant of the disease. Granulomatous mycosis fungoides (GMF) is also a rare type of CTCL. No particular clinical criteria are available for the diagnosis of GMF, because of its variable presentations, and so the detection of GMF is primarily considered as a histopathological diagnosis. Rarely, a co-existence of more than one clinical or histopathological feature of mycosis fungoides may be present. To the best of our knowledge this is the first report of MF that shows the simultaneous co-existence of more than one clinical and histopathological variant of MF. We present a 29-year-old female with clinical presentations of both classic and hypopigmented mycosis fungoides (MF), and also the histopathological features of the classic and granulomatous types of the disease.